The formation of shoshonitic magma and its relationship to porphyry-type mineralisation: the Maronia pluton in NE Greece - Schaarschmidt, Anna; Klemd, Reiner; Regelous, Marcel; Voudouris, Panagiotis C.; Melfos, Vasilios; Haase, Karsten (Lithos, 2021)
The Oligocene shoshonitic Maronia pluton in NE Greece is part of an age-progressive belt of calc-alkaline intrusions and associated with a porphyry Cu-Mo±Re±Au mineralisation. We present new data on mineral and whole rock compositions as well as Sr, Nd and Pb isotopes of the monzodioritic to granitic rocks from Maronia, including the mineralised microgranite, which crosscuts the main intrusion. The age progression of the plutons in NE Greece follows the southward-directed trench retreat implying that the magmas formed during subduction of continental lithosphere after the closure of the Pindos ocean. The shoshonitic magmas of Maronia were generated by hydrous melting of a phlogopite-bearing mantle that was enriched by 3-5% of slab-derived sediment melts. A lower degree of melting controls the higher K, LILE and incompatible element contents of the shoshonitic magmas in comparison to the neighbouring calc-alkaline magmas. The mafic shoshonitic rocks in NE Greece contain much higher P2O5 contents than the associated calc-alkaline magmas, which probably reflects subducted phosphate-rich sediments in their source. Constant Sr- and Nd-isotopes with increasing SiO2 contents imply minimal crustal assimilation and that felsic magmas including the mineralised porphyritic granite were generated by fractional crystallisation of mafic magmas. Amphibole and apatite analyses provide evidence for the intrusion of S-poor, Cl-rich magmas at 5 to 6 km depths, followed by rapid uplift and exsolution of magmatic fluids. Late granitic dikes at Maronia indicate that volatiles, sulphur and metals became enriched during the late stages of the magma evolution.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Magmatic sulphur; Metal budget; Porphyry copper deposits; Sediment subduction; Shoshonitic magmatism